Development of a novel prognostic score for breast cancer patients using mRNA expression of CHAC1. (October 2017) - Jahn, Beate; Arvandi, Marjan; Rochau, Ursula; Fiegl, Heidi; Goebel, Georg; Marth, Christian; Siebert, Uwe
Aim: To develop a prognostic score for primary breast cancer patients integrating conventional predictors and the novel biomarker CHAC1 to aid adjuvant chemotherapy decisions.Patients & methods: A prognostic score for overall survival was developed using: conventional predictors from a dataset of 1777 patients and the weight of CHAC1 mRNA expression from an independent dataset of 106 patients using multivariate Cox regression.Results: The new score includes: CHAC1 mRNA expression, age, tumor size, HER2 neu status, lymph node status and degree of malignancy. Using a cut-off value of 11 score points, 10-year survival was 82% in low-risk (n = 34) and 43% in high-risk patients (n = 72). The addition of CHAC1 resulted in 16% reclassification.Conclusion: Including CHAC1 in prognostic prediction may aid (and change) personalized treatment selection.